METODE MEMAHAMI MAKSUD SYARI’AH - Djaenab Djaenab (Sulesana, 2013)
purposein establishingHislaws. Therefore,efforts touncoverandunderstand thembythe scholarsdividedthefour methodswithdifferentshades ofunderstanding, namely: Methods lafzi atau al-Zahiri, method Ma’nawi (contextual), Understanding themeaning ofthe methodbeyondnashor themethod offreethought patterns, methodsMergerbetween lafziyah and Ma’nawiyah.